Mandapa (pillared hall) of the Mahanaleshwar Temple with three Devakoshthas (niches) - Temples of India Project Team (Jio Institute, 2024)
The north-facing lateral transept of the mandapa (pillared hall) of the Mahanaleshwar Temple has three devakoshthas (niches), of which the two on the right are seen here. Amongst them, the devakoshthas at the centres of the dwarf pillars house an icon of Vishnu and, on the right, an image of Gajalakshmi. Vishnu is shown with a Garuda near his foot and the goddess has two elephants above her bust. The wall frieze that separates the devakoshthas consists of a pilaster motif interlaced with icons of surasundaris (celestial damsels). The mouldings of the plinth match the mandapa of the temple.